FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR DI RUANG MEDICAL RECORD RSUD PARIAMAN - Rahmawati, Lisa; Ningsih, Mahdalena Prihatin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: FACTORS ASSOCIATED WITH GENESIS NEONATAL ASPHYXIA IN PARIAMAN HOSPITAL MEDICAL RECORD ROOM. There are many factors that can cause the asfiksia of the newborn, whether it were fakctor of mother like primi tua, poor obstetric history, grande multipara, gestasi period, anemia and maternal illness, premature rupture of membranes, long parturition, narrow pelvis, intrauterine infection, factor of fetus like fetal distress, multiple pregnancy, breech, tranverse position, birth weight, and factor placental. The occurance of asfiksia in newborn in RSUD Pariaman is relatively high, that were 438 babies. Research objective: to know about factors that related to asfiksia in newborn in medical record room RSUD Pariaman. Research type: analiytic descriptive with retrospective aproach. The research population is all babies in RSUD Pariaman. Sampling was done by using total sampling technique for 971 people. Data collection was done by using documentation sheet. Data were analyzed using univariate and bivariate. The result showed that there was significant relationship between poor obstetric history with asfiksia occurance, premature rupture of membranes with asfiksia occurance, and birth weight with asfiksia occurance. As the conclusion, that was significant relationship between obstetric history, premature rupture of membranes, and birth weight with asfiksia. Key words: Asphyxia, Newborn